ARCHAIC FEATURES OF WORD ORDER AND WORD-ORDER INNOVATIONS IN THE TORRE AND RESIAN DIALECTS OF SLOVENE - Zuljan Kumar, Danila (Slavia Centralis, 2026)
The aim of this paper is twofold: first, to identify word-order features in the Torre and Resian dialects of Slovene that can be attributed to the influence of contact Romance languages; and second, to compare the ordering of inflected clitics within the clitic cluster across the two linguistic systems. The first part examines the placement of agreeing adjectival modifier within the nominal phrase, the focalized sentence constituent, and the positioning of clitics in declarative and imperative clauses. The second part addresses the movement – or lack thereof – of clitic forms of the verb to be in the present and future tense toward the beginning of the clitic cluster, the movement of the clitic bi, and the placement of non-nominative pronominal clitics within complex verbal forms.
Keywords: dialect syntax; word order; Slovene; Torre dialect; Resian dialect; clitics; language contact